2016
DOI: 10.17567/dfd.95782
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Strength of Soldered and Laser Welded Orthodontic Bands and Wires With and Without Filling Material: A Preliminary Report

Abstract: Aim:The aim of this study was to compare the fracture strength of orthodontic band-wire joints made by conventional silver soldering and different laser welding procedures and detect the effects of the surface preparation with sandblasting to the fracture strength of the laser welding. Materials and Methods: Forty specimens were divided to four groups (n=10); group 1; brazing with silver solder, group 2; laser welding (Desktop Compact Laser, Dentaurum,Germany) with sandblasting (with 50 μm aluminum oxide), gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Another point of concern for silver soldered SMs is the reduced corrosion resistance as a result of galvanic corrosion between different types of metals. High corrosion rates can influence mechanical strength and biocompatibility [4,13] .…”
Section: Most Mechanical Failures Of Fixedmentioning
confidence: 99%
See 1 more Smart Citation
“…Another point of concern for silver soldered SMs is the reduced corrosion resistance as a result of galvanic corrosion between different types of metals. High corrosion rates can influence mechanical strength and biocompatibility [4,13] .…”
Section: Most Mechanical Failures Of Fixedmentioning
confidence: 99%
“…On the contrary, both safety issues and mechanical considerations encourage the shift to laser welding.Laboratory tests revealed that laser welding provided superior mechanical strength and microhardness of joints compared to silver solder [5,13] .…”
Section: Most Mechanical Failures Of Fixedmentioning
confidence: 99%